Synthesis, biological evaluation and molecular docking studies of flavonol-3-o-β-d-glycoside as a potential inhibitor of sars-cov-2 main protease (3clpro) in drug development for covid-19 - Çelik, Gonca; Alpay Karaoğlu, Şengül; Suyabatmaz, Şeyma; Bozdeveci, Arif; Tatar Yılmaz, Gizem; Yaylı, Nurettin; Çopur Çiçek, Ayşegül (My University, 2025)
The COVID-19 pandemic began in March 2020 and has affected many countries and infected over a million people. It has had a serious impact on people's physical and mental health, daily life and the global economy. Today, many drugs show limited efficacy in the treatment of COVID-19 and studies to develop effective drugs continue. Here, we aim to the synthesise and characterise of the flavonol-3-O-glycoside derivatives, the following and evaluated molecular docking studies with antimicrobial activity, inhibition of SARS-CoV-2 main protease enzyme (3CLpro) and nuclease activity. Molecular docking simulations of the synthesized flavonol-3-O-glycoside derivatives, especially compounds 5a, 5d, 5h, 5i and 5m, showed a stronger interaction with SARS-CoV-2 3CLpro in the active site. Two compounds from the target compounds, 5h and 5m, were found to be specifically effective against M. smegmatis and yeasts. In particular, compounds 5a, 5d, 5h, 5i and 5m, which exhibited high activity against the SARS-CoV-2 main protease enzyme, were found to be effective at low concentrations. We determined the IC50 values for the compounds that showed an inhibitory effect as well as their nuclease activities, which further emphasising the potential of our results. Among these, compound 5d showed a significant competitive inhibitor of 3CLpro. Furthermore, nuclease activity studies identified compound 5d as the most potent. The above results suggest that the flavonol-3-O-glycoside derivatives could be promising new antiviral agents for the development of 3CLpro inhibitors to combat COVID-19.
Keywords: Antimicrobial Activity; COVID-19; Flavonol-3-O-Glycoside; Molecular Docking; Nuclease Activity; SARS-Cov-2